Hepatocellular Carcinoma 2019
DOI: 10.15586/hepatocellularcarcinoma.2019.ch2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Tumor Microenvironment in the Development and Progression of Hepatocellular Carcinoma

Abstract: There is growing evidence that supports the role of the tumor microenvironment in the development and progression of hepatocellular carcinoma. The tumor microenvironment is composed of cellular components, bioactive substances, and extracellular matrix comprising of proteins such as collagens, proteoglycans,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 106 publications
0
23
0
Order By: Relevance
“…To date, pharmacological approaches in search for new drugs have focused mainly on oncogenic signaling pathways, while the tumor microenvironment (TME), in which tumors develop, has only recently become an important target for anti-cancer therapies. The TME contributes to three key mechanisms of cancers to evade immune recognition—(1) allowing the (epithelial) cancer cells to thrive in a chronically inflamed environment by shifting the micromilieu towards immunosuppression; (2) promoting cancer growth via inducing angiogenesis in a hypoxic environment; (3) facilitating active immune evasion of the cancer cells [ 10 ]. The cellular TME has been best studied and first successful therapies have emerged based on the development of checkpoint inhibitors that block immune suppressive signaling between myeloid and T cells [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, pharmacological approaches in search for new drugs have focused mainly on oncogenic signaling pathways, while the tumor microenvironment (TME), in which tumors develop, has only recently become an important target for anti-cancer therapies. The TME contributes to three key mechanisms of cancers to evade immune recognition—(1) allowing the (epithelial) cancer cells to thrive in a chronically inflamed environment by shifting the micromilieu towards immunosuppression; (2) promoting cancer growth via inducing angiogenesis in a hypoxic environment; (3) facilitating active immune evasion of the cancer cells [ 10 ]. The cellular TME has been best studied and first successful therapies have emerged based on the development of checkpoint inhibitors that block immune suppressive signaling between myeloid and T cells [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In each case the ECM supports the growth of tumor nodules and forms the interface between the cancer and the nontumorous tissues of the body. In advanced cancer, the TME usually mediates immunosuppression and transcriptional alterations in the TME were found to be more predictive for the survival of HCC patients than in the tumor epithelia themselves, underlining a key role of the TME in cancer progression [ 10 ]. Importantly, apart from the immune cells in the tumor connective tissue that are skewed towards immunosuppression, the tumor myofibroblasts, that is, the cancer associated fibroblasts (CAF), support cancer growth by secreting pro-cancerous, immunosuppressive and pro-angiogenic ECM components and growth factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional treatment does not meet the requirements for longer survival time and higher quality of life. An increasing number of studies revealed that the tumor microenvironment and the expression of immune checkpoint molecules accelerated the progression of cancers ( 8 10 ). The use of immune checkpoint inhibitors markedly improved the prognosis of cancers (e.g., melanoma) ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The following studies investigate these dual roles in relation to the activation of HSCs in the hepatic TME. Budhu and Wang, 2006;Fu et al, 2007;Hoechst et al, 2008;Jeong et al, 2011 Cytokines (IL-6, IL-8, IL-22): small proteins involved in a range of cell signaling that help drive fibrosis, HSC activation, and contribute to angiogenesis Chiu et al, 2014;Sevic et al, 2019 Cancer associated fibroblasts: type of cancer stromal cell critical to tumorigenesis regulation by possessing the ability to remodel the ECM and secrete proteins such as cytokines and VEGF Yin et al, 2019 Both cellular and non-cellular components cooperate in the hepatic TME to aid in hepatocarcinogenesis.…”
Section: Micro-rna Involvement In Hsc Activation In the Hepatic Tmementioning
confidence: 99%